Legal Protection Of Consumers Against Misuse Of Personal Data By Business Actors In The Digital Era - Yuniar Rahmatiar (Jurnal Ekonomi, 2024)
Amidst the rapid development of information technology, consumer personal data has become a very valuable asset for business actors, but this also increases the risk of misuse. This study aims to analyze various forms of Consumer Legal Protection against Misuse of Personal Data by Business Actors in the Digital Era. The research method used is normative juridical with a legislative approach and case studies. The research results show that the misuse of personal data by business actors in the digital era poses serious risks to consumers, including unauthorized data collection, fraud, and discrimination, which can damage the trust and reputation of the company. The losses from this abuse are not only financial, but also emotional and reputational, impacting individuals' mental health and their access to financial services. In Indonesia, consumer legal protection against personal data abuse is regulated in the 1945 Constitution of the Republic of Indonesia and Law Number 27 of 2022 concerning Personal Data Protection, which affirms the individual's right to feel safe. Controllers and processors of personal data are responsible for maintaining the confidentiality and integrity of data, while the appointment of a competent data protection officer is essential to ensure compliance with regulations and minimize violations. Through these steps, it is hoped that personal data protection can be implemented effectively, creating a safe digital environment and increasing consumer trust .